Advancing Sustainable Development Goals through Character Education and Social Studies in Japanese Schools - Andhy Surya Hapsara; Charlotte Adams; Nhung Thi-Cam Nguyen; Mark Vencint Tapia Lubi; Siti Muti’ah; Fui Byn Liew; Thy Visal; Abd-Asit Hayeekhade; Chandy Xaiyalath; Yusuke Nakashima (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Character education is increasingly recognized as a critical component in developing individuals who are not only academically proficient but also possess strong moral and ethical values. This study examines the integration of social studies, character education, and the Sustainable Development Goals (SDGs) within Japan's educational system, focusing on how these elements equip students with the skills and values necessary to address contemporary global challenges. Employing a qualitative descriptive approach, the study combines field research and literature analysis. The literature review provided a foundation for analyzing the issues under study, while field research was conducted from November 17 to 24, 2024, in Tokyo City and Tokushima Prefecture, Japan. The findings reveal that 17 SDGs components are embedded within Japan's educational practices, including competency in Education for Sustainable Development (ESD). Moreover, character education in Japanese schools significantly contributes to nurturing individuals with strong ethical and responsible values, empowering them to act as agents of change in addressing the complexities of a globalized world, particularly in responding to environmental issues. Integrating character education and social studies with the SDGs is identified as a strategic framework for shaping a better future for younger generations. This model offers valuable insights for educational systems worldwide to consider in their efforts to enhance character education.